Assessment of cardiac complication in diabetic patient of rural India - Ahmad, E.; Singh, A.; Chaudhary, R. R.; Sarda, M. S. (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus (DM) is a common endocrine disorder affecting approximately 382 million people worldwide. Diabetes mellitus (DM) is group of metabolic disorder in which glucose is underutilized, thus producing hyperglycemia resulting from a defect in insulin secretion, action, or both. Cardiovascular disease is the most common cause of death and disability among people with diabetes. The cardiovascular disease that accompany diabetes include angina, myocardial infarction (heart attack), Stroke, peripheral artery disease and congestive heart failure. In people with diabetes, high blood pressure, high cholesterol, high blood glucose and other risk factors contribute to the increased risk of cardiovascular complications. Method: This study was conducted to determine the cardiac complication in diabetic patient of rural India. It was Cross sectional retrospective study, done in between period of January 2018 to December 2019. Result: In the present study authors found that 47.7% patients have Coronary artery disease (CAD), Silent 21.6% have myocardial ischemia (SMI), 36% Diastolic dysfunction (DF), 28.8% have Systolic dysfunction (SDF). Conclusion: In this study authors found that wide spectrum of cardiac complications in diabetic patients ranging silent myocardial ischemia to heart failure. CAD was the most common complication including silent myocardial ischemia (SMI) which is the one of the major concern of rural diabetic population which need proper screening by exercise treadmill test.